THE VISUAL ANALYSIS OF MUSLIMAH CLOTHING STYLE IN JAVA (15-20 th CENTURY) - Indrianti, Pingki; Kurniawan, Oki; Hassan, Faridah Hj (UIN Maulana Malik Ibrahim Malang, 2021)
Islam entered Indonesia in the 7th century and began to spread out in the 13th century with the establishment of Demak Sultanate. After the expansion of Islamic kingdoms or Sultanates, the spread of Islam in Java and Sumatra strengthened the application of Islamic law (Sharia). It was slowly replacing customary law yet still maintaining and even acculturating the local culture, with no exception concerning Muslimah clothing style (hijab or (jilbab). This non-interactive qualitative research analyzed the factual data related to the transformation of Muslimah clothing from the 15th to the 20th century focusing on Java island. The data were analyzed using the Fashion Design Components theory proposed by Stone (2006) and Seivewright (2012) to get detailed visualization of Muslimah clothing style in those eras. The result showed that Islamic values influenced the clothing style of Javanese Muslim women in terms of silhouettes, colors, details, and materials (textures) without neglecting the local culture.Islam masuk ke Indonesia pada abad ke-7 dan mulai menyebar pada abad ke-13 Masehi dengan berdirinya Kerajaan Islam Demak. Penerapan hukum Syariah Islam secara perlahan menggantikan hukum Adat namun demikian tetap mengakomodasi bahkan berkakulturasi dengan budaya setempat, termasuk dalam hal penerapan busana Muslimah (jilbab). Penelitian ini bertujuan untuk menganalisis visualisasi busana Muslimah di Indonesia khususnya di Jawa pada abad 15-20 Masehi. Penelitian kualitatif non-interaktif ini menggunakan pendekatan deskriptif yang menekankan pada data-data faktual terkait perkembangan busana wanita Muslim. Data dianalisis menggunakan teori elemen desain mode (the components of fashion) yang terdiri dari siluet, warna, detail, dan tekstur untuk mengetahui gambaran bentuk busana Muslimah pada masa tersebut. Hasil penelitian menunjukan ajaran Islam mempengaruhi gaya berpakaian wanita Muslim Jawa, baik dari segi elemen visual bentuk (siluet), warna, detail, dan material (tekstur), namun demikian tetap mempertahankan budaya lokal yang berlaku.